2022
DOI: 10.3847/1538-4357/aca479
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Energy Transfer and Proton–Electron Heating in Collisionless Plasmas

Abstract: Despite decades of study of high-temperature weakly collisional plasmas, a complete understanding of how energy is transferred between particles and fields in turbulent plasmas remains elusive. Two major questions in this regard are how fluid-scale energy transfer rates, associated with turbulence, connect with kinetic-scale dissipation, and what controls the fraction of dissipation on different charged species. Although the rate of cascade has long been recognized as a limiting factor in the heating rate at k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 95 publications
1
6
0
Order By: Relevance
“…We made two crucial simplifications in the analysis: (a) the only source of energy that heats the upstream and downstream plasma is the cascaded turbulent energy and (b) all this energy is absorbed by the protons only. On the basis of numerous studies which investigate SW heating (Smith et al 2001;Cranmer et al 2009;Adhikari et al 2017) and the partitioning of the cascading energy into protons and electrons (Howes 2010;Matthaeus et al 2016;Roy et al 2022), we suggest that both of these assumptions are well-supported. However, we acknowledge that the change in the ratio of heating rates of protons, Q p, and electrons, Q e , R Q = Q p /Q e , may influence the results of our analysis, e.g., Matthaeus et al (2016) 13)), i.e., an absolute distance of a plasma parcel with respect to L1.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We made two crucial simplifications in the analysis: (a) the only source of energy that heats the upstream and downstream plasma is the cascaded turbulent energy and (b) all this energy is absorbed by the protons only. On the basis of numerous studies which investigate SW heating (Smith et al 2001;Cranmer et al 2009;Adhikari et al 2017) and the partitioning of the cascading energy into protons and electrons (Howes 2010;Matthaeus et al 2016;Roy et al 2022), we suggest that both of these assumptions are well-supported. However, we acknowledge that the change in the ratio of heating rates of protons, Q p, and electrons, Q e , R Q = Q p /Q e , may influence the results of our analysis, e.g., Matthaeus et al (2016) 13)), i.e., an absolute distance of a plasma parcel with respect to L1.…”
Section: Discussionmentioning
confidence: 83%
“…Roy et al (2022) have shown that R Q scales with the sum Q p + Q e ∼ ò. Thus, the DR of IP shocks should exhibit larger proton heating.…”
mentioning
confidence: 99%
“…(1) The time evolution of the thermal energy has been established for the simulations in Figure 1, but the corresponding analysis is not available for the in situ data, where it is not possible to follow the time evolution of an isolated plasma parcel. Lacking a direct way to compute the thermal energy increase over time, we resort to examination of the pressurestrain interaction related to the conversion of fluid kinetic energy into thermal energy, which is also supported by Pezzi et al (2019), Yang et al (2022), Bacchini et al (2022), Roy et al (2022). ( 2) According to Equations (1) and (2), in PIC simulations the spatial average over the entire periodic simulation domain represents precisely how much thermal energy is gained because all transport terms vanish exactly.…”
Section: Mms Observation Results In the Magnetosheathmentioning
confidence: 99%
“…For example, the findings of Cranmer (2009) and Hughes et al (2014) favor stronger ion heating, while Bandyopadhyay et al (2021) and Yang et al (2022) report stronger electron heating. As suggested in early studies, the partitioning of heating between ions and electrons could depend on the turbulence amplitude (Stawarz et al 2009;Wu et al 2013;Matthaeus et al 2016;Hughes et al 2017;Roy et al 2022) and plasma β (the ratio of thermal to magnetic pressure) (Quataert 1998;Howes 2010;Klein et al 2017;Parashar et al 2018;Vech et al 2017;Kawazura et al 2019;Schekochihin et al 2019). To quantify the distribution of energy between species, there is an increasing awareness that the pressure-strain interaction (Yang et al 2017a(Yang et al , 2017b(Yang et al , 2019Pezzi et al 2019;Hunana et al 2019;Matthaeus et al 2020;Lapenta et al 2020;Yang et al 2022;Hellinger et al 2022) is a direct way to identify incompressive versus compressive heating (Chasapis et al 2018;Du et al 2018;Pezzi et al 2020;Wang et al 2021;Zhou et al 2021;Bandyopadhyay et al 2021), as well as ion versus electron heating (Sitnov et al 2018;Bandyopadhyay et al 2021;Roy et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…2020; Roy et al. 2022), large-scale pressure anisotropy can also heat collisionless electrons (Sharma et al. 2007), meaning that the cascade efficiency – and thus magneto-immutability – could directly control the ion-to-electron heating ratio.…”
Section: Introductionmentioning
confidence: 99%